Music in Arabia : Perspectives on Heritage, Mobility, and Nation - Boulos, Issa, 1968-; Danielson, Virginia; Rasmussen, Anne K.; Hassan, Scheherazade; al-Mulaifi, Ghazi; Lambert, Jean; AlSalhi, Ahmad; Bilkhair, Aisha; Ayari, Yassine; al-Harthy, Majid H. (Indiana University Press, 2021)
With the work of resident heritage practitioners set alongside that of Western researchers, Music in Arabia offers both context and content to clarify how music articulates identity and nation among multiethnic, multiracial, and multinational populations.